2017
DOI: 10.1016/j.celrep.2016.12.063
|View full text |Cite
|
Sign up to set email alerts
|

A Tissue-Mapped Axolotl De Novo Transcriptome Enables Identification of Limb Regeneration Factors

Abstract: SUMMARY Mammals have extremely limited regenerative capabilities; however, axolotls are profoundly regenerative and can replace entire limbs. The mechanisms underlying limb regeneration remain poorly understood, partly because the enormous and incompletely sequenced genomes of axolotls have hindered the study of genes facilitating regeneration. We assembled and annotated a de novo transcriptome using RNA-sequencing profiles for a broad spectrum of tissues that is estimated to have near-complete sequence inform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
679
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 819 publications
(686 citation statements)
references
References 82 publications
(71 reference statements)
7
679
0
Order By: Relevance
“…Functional analysis of axolotl development, physiology and regeneration is facilitated by the availability of tissue-and time-dependent gene expression profiles [28][29][30]36 . The axolotl genome provides a foundation for applying methods such as chromatin immunoprecipitation with sequencing (ChIP-seq) or assay for transposase-accessible chromatin using sequencing (ATAC-seq) to investigate the genomic basis of gene regulation during regeneration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Functional analysis of axolotl development, physiology and regeneration is facilitated by the availability of tissue-and time-dependent gene expression profiles [28][29][30]36 . The axolotl genome provides a foundation for applying methods such as chromatin immunoprecipitation with sequencing (ChIP-seq) or assay for transposase-accessible chromatin using sequencing (ATAC-seq) to investigate the genomic basis of gene regulation during regeneration.…”
Section: Discussionmentioning
confidence: 99%
“…Recent functional work has highlighted the role of diverged gene or protein function during regeneration [25][26][27] . Analysis of published tissue-enriched datasets 28 , combined with regeneration time courses 29,30 and our own transcriptional profiling of 22 tissues, identified five transcripts that are upregulated in the limb blastema (the mass of proliferating cells involved in regenerating the limb) with orthology limited to non-amniote vertebrates (Supplementary Information section 7). One of these protein sequences shows a weak similarity to tectorin, a basement membrane component normally found in the inner ear, consistent with studies that implicate extracellular matrix components with having an important role in limb regeneration 31,32 .…”
Section: Species-restricted Genes In Regenerationmentioning
confidence: 99%
“…Bryant, et al. (2017) have assembled an axolotl transcriptome that identifies transcripts enriched in individual limb tissues and which distinguishes blastemas from differentiated limb tissues. This study revealed two highly upregulated genes, the RNA binding protein gene cirbp and the serine protease inhibitor gene kazald1 .…”
Section: Formation Of the Accumulation Blastemamentioning
confidence: 99%
“…In the past eleven years, both transgenesis [4] and genome editing [58] have been successfully performed in axolotls in several laboratories. Retroviral infection, which results in genomic integration, has also been demonstrated in embryos and in larval and adult limbs [9, 10]. Localized genome editing has now been developed, allowing for study of mutant cells in vivo without necessarily waiting for homozygous loss-of-function mutants [10].…”
Section: Why Use the Axolotl?mentioning
confidence: 99%
“…Retroviral infection, which results in genomic integration, has also been demonstrated in embryos and in larval and adult limbs [9, 10]. Localized genome editing has now been developed, allowing for study of mutant cells in vivo without necessarily waiting for homozygous loss-of-function mutants [10]. Genome engineering is poised to be the definitive tool for doing bona fide loss-of-function genetics in axolotls and to finally allow for direct attribution of wild-type gene function in the process of limb regeneration.…”
Section: Why Use the Axolotl?mentioning
confidence: 99%